Description of Tovomita clarkii (Clusiaceae), an endemic species from Venezuela - Marinho, Lucas C.; Gahagen, Benjamin; Amorim, André M. (Phytotaxa, 2016)
Tovomita clarkii is a species endemic to Venezuela. The name of this species was first suggested in 1989 by J.J. Pipoly while labeling herbaria material; however, this species was never officially described. Besides the description, here we provide data on the distribution and conservation status of this new species, and discuss its morphological affinities.